THE TAX SYSTEM OF UKRAINE AND THE EU COUNTRIES: A COMPARATIVE ASPECT (Economic journal of Lesya Ukrainka Volyn National University, 2024)
Introduction. The tax system is one of the main tools of economic policy, which allows to regulate financial flows, stimulate economic development and ensure the stability of public finances. Comparing the tax systems of Ukraine and the European Union countries is important for understanding the ways of integration and adaptation of the Ukrainian economy to European standards, especially considering Ukraine's intentions to join the EU.The purpose of the article. The goal of the research is to identify the peculiarities of the functioning of the tax system of Ukraine and the tax systems of the European Union and, on the basis of a comparative analysis, to identify their positive and negative characteristics.Methods. The research methodology involves the use of a comprehensive approach, which includes the analysis and systematization of sources of scientific and practical literature, regulatory and legal framework and analytical data. The research uses methods of comparative analysis to determine the advantages and disadvantages of the analyzed tax systems, a system approach to determine the conceptual basis of the functioning of the tax system of Ukraine and the EU countries, as well as a method of logical generalization to formulate conclusions. At the same time, the article uses a tabular method to visually present the research results.Results. The article defines the necessity of researching the tax systems of the countries of the European Union and the tax system of Ukraine. It was found that the level of taxation in Ukraine corresponds to the average European indicators. An analysis of rates for value added tax, personal income tax, and income tax in Ukraine and in such countries of the European Union as Germany, Spain, Italy, France, Poland and others was carried out. The analysis showed that Ukraine currently has one of the lowest tax rates for the three main taxes among the European countries under review. It has been proven that there is no ideal taxation system. The main advantages and disadvantages of the investigated tax systems are determined.Conclusions. The importance of forming an optimal taxation system in Ukraine as a key element of the socio-economic development of the country in the conditions of military aggression is proven. The main imperatives for the development of the tax system of Ukraine in the conditions of European integration processes are proposed.
Keywords: taxes; tax system; taxation; tax burden; European Union; efficiency.